Chief Financial Officer Educational Background and Company Performance (Department of Accounting, Faculty of Economics, Universitas Negeri Semarang, 2022)
Purpose: This study aims to examine the relationship between the Chief Financial Officer (CFO) education background and company performance. We identified educational background levels, namely bachelor, master, doctorate, and certification.Method: This study uses 1176 sample companies listed on the Indonesia Stock Exchange IDX in2014-2017. This study uses purposing sampling and testing Ordinary Least Square Regression STATA 14.Finding: This study found that companies with only a CFO with a specific educational background of CFO is significantly impact on company performance. Master’s educational experience and certification show a negative relationship while the rest are unrelated to company performance, but bachelor and doctoral degree show otherwise.Novelty: This research contributes empirically to the development of the literature. It practically provides consideration for stakeholders to pay more attention to the educational qualifications of CFOs regarding the company’s spatial reporting policies.